A modified styrene-butadiene latex
By introducing a lithium sol acid stone sol into the styrene butadiene latex to form a core-shell structure, the problem that styrene butadiene latex is difficult to take into account both bond strength and gloss in paper coating in the prior art. High woven strength, excellent gloss and water resistance are achieved, and stability is improved.
Patent Information
- Application Number
- CN202410144639.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-01
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-02-01
AI Technical Summary
The existing styrene butadiene latex is difficult to take into account both bond strength and gloss in paper coating. At the same time, the high-speed coating and printing technology puts higher requirements on the stability of the latex.
Using emulsion polymerization technology, lithium saponite acidified sol is introduced into the styrene butadiene copolymer system to form a composite modified styrene butadiene latex with a core-shell structure. This method uses lithostone particles to form a protective layer on the periphery of the latex particles to stabilize the emulsion and improve the physical and optical properties of the latex.
The high hair-pull strength, excellent gloss and water resistance of the latex are achieved, while improving mechanical stability, chemical stability and storage stability, ensuring that there is no solidification in 10-35°C for 180 days.
Smart Images

Figure BDA0004693747610000061 
Figure BDA0004693747610000131
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of styrene butadiene latex, in particular to a modified styrene butadiene latex. [Background technology]
[0002] With the development of science and technology and the continuous improvement of people's living standards, the demand for high-end coated paper and coated board paper has grown rapidly, and non-woven fabrics and chemical fiber products are used in large quantities, resulting in a continuous increase in the demand for styrene-butadiene latex for paper coating and non-woven fabrics / cardboard and carpet backing, expanding the main application market of styrene-butadiene latex.
[0003] Styrene butadiene latex is an emulsion polymer containing monomers such as styrene, butadiene, and acrylic acid, which is formed by the action of initiators and emulsifiers and water. Styrene butadiene latex is generally synthesized by emulsion polymerization technology at high temperatures of 65-95°C and pressures of about 1bar-6bar. In paper and paperboard coatings, styrene butadiene latex has many uses, such as coating adhesives in paper coating. Styrene butadiene latex enhances the binding force of pigments, making paper smoother, harder, and more waterproof, and its price is also competitive than other types of adhesives. Due to its ability to bind pigments and fillers and its strength, it has become the preferred polymer coating for paper.
[0004] As a water-based polymer emulsion, styrene butadiene latex has excellent film-forming and adhesive properties, and is cheap, safe, and environmentally friendly. It has become the most widely used film-forming substance in papermaking and chemical fiber materials. However, in many applications of styrene butadiene latex, especially in paper coating, it is often difficult to balance the bonding strength and glossiness of coated paper products and make both of them at an excellent level. At the same time, the high-speed coating and printing technologies have put forward higher stability requirements for coating latex. Although the use of efficient emulsifiers or increasing the amount of emulsifiers can solve the stability problem of latex coatings on high-speed paper machines, it inevitably leads to a significant decrease in paper printing performance and water resistance. To solve these problems, functionalization of coating latex has become an important method to improve its application performance. An effective method is to perform composite modification on styrene butadiene latex. Such as Chinese patents 201910648550.7, 201910648556.4, 201910648658.6, 201910648534.8 and other core-shell or multiphase structured butadiene styrene copolymer latexes. These modifications provide an essential and expanding market for synthetic latex and improve the performance of the final product.
[0005] Among its many composite modification methods, the composite material of inorganic nanomaterial modified styrene butadiene latex is a research direction of modified styrene butadiene latex. Inorganic material modified butadiene styrene copolymer latex includes adding organic clay as filler to form styrene butadiene hybrid polymer or nanocomposite material. Inorganic nanomaterial clay is often used to prepare inorganic / polymer nanomaterial composite materials. In order to produce good nanocomposites, clay should be treated before being used in polymers. Because clay is hydrophilic in nature, it is difficult to disperse in the polymer matrix. To change the compatibility of clay with the polymer main body, clay can be dispersed in the polymer matrix; in addition, because there are cations in the clay layer, and styrene butadiene latex is an anionic polymer, direct mixing of the two will affect the stability of styrene butadiene latex. For this reason, the modification of clay should first break the aggregation structure of clay, usually through cation exchange technology, reduce the cations on the surface of the clay layer to make it more organic polymer-friendly; alkyl phosphorus type and imidazole surfactants are commonly used as clay modification agents to prepare nanocomposites. In recent years, solid particle stabilized emulsions, also known as Pickling emulsions, have developed rapidly and attracted widespread attention because they avoid the toxicity and negative effects of surfactants (such as foaming, toxicity, and impact on material properties) and have unique interfacial particle self-assembly effects.
[0006] Patent CN201711167541.3 prepares a water-based acrylic resin / lithium bentonite organic-inorganic composite leather finishing agent, which is characterized in that nanoparticle lithium bentonite is used as a stabilizer instead of a traditional organic surfactant, and an emulsion polymerization technology is used to prepare a water-based acrylic resin / lithium bentonite composite leather finishing agent with an acrylate polymer as a core and inorganic nanoparticles as a shell. This not only avoids the use of organic surfactants in traditional emulsion polymerization methods, solves the toxicity problem of organic emulsifiers and their negative impact on the late film-forming properties of the emulsion, but also the stabilizer lithium bentonite nanoparticles used are a nanoclay with a lamellar structure, which can also be used as an enhancing modifier for acrylic resin, significantly improving the mechanical properties, wear resistance and thermal stability of the finishing agent, and giving the coating film good resistance to ultraviolet aging. However, lithium bentonite is hydrophilic and difficult to disperse in a polymer matrix. It needs to be specially treated to change its hydrophilic properties so that it is compatible with the polymer matrix. Only when lithium bentonite is dispersed into a polymer matrix can it exert its proper modification performance. However, this method does not disclose the modification method, nor does it investigate the key properties of the composite emulsion with nanoparticle lithium bentonite as a stabilizer, such as mechanical stability, chemical stability, and storage stability. We note that lithium bentonite is a highly hydrophilic, artificially synthesized layered silicate with a nano-lamellar structure. Its particle size is concentrated in the range of 25 to 50 nm, and the thickness of the lamella is 1 nm. It is size-controllable and highly hydrophilic. It can be peeled into a lamellar structure in water, and finally forms a colorless and transparent colloidal dispersion. Therefore, it has been widely used as an additive and rheological agent in industrial and consumer products such as coatings, varnishes, printing, and toothpaste, and its colloidal properties give it unique advantages in stabilizing emulsions or latex particles. In fact, there have been some research reports on the modification of styrene-butadiene polymers with nano clay, such as patent CN200810200760.1, which uses sodium bentonite to modify styrene-butadiene latex. The sodium bentonite and styrene-butadiene latex are mixed in a mechanical blending manner, with a mixing ratio of 10%. The obtained bentonite-modified styrene-butadiene latex improves the bonding performance of the latex. However, there has always been a problem of poor compatibility between inorganic nano clay and organic polymers. The patent does not examine the key properties of the obtained composite emulsion, such as mechanical stability, chemical stability and storage stability. The inventor's latest research found that the use of a polymerization method can solve this problem well, and the solid particle emulsifier that stabilizes the emulsion has the advantages of being cheap, non-toxic, and pollution-free, and the prepared polymer emulsion does not need to undergo complex post-processing.
[0007] Based on the above technical conditions, the inventors propose the following technical solutions. [Summary of the invention]
[0008] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a modified styrene-butadiene latex.
[0009] To solve the above technical problems, the present invention adopts the following technical scheme: a modified styrene-butadiene latex, which is composed by weight of: 37-52% of C4-C5 aliphatic conjugated diene monomers; 40-58% of vinyl unsaturated monomers; 2.5-6.0% of acidified hectorite sol; 1.5-4.0% of unsaturated carboxylic acid monomers; and 0.5-3.0% of unsaturated amide monomers.
[0010] Furthermore, in the above technical solution, the C4-C5 aliphatic conjugated diene monomer is selected from 1,3-butadiene or a mixture of 1,3-butadiene and isoprene.
[0011] Furthermore, in the above technical solution, the vinyl unsaturated monomer is selected from styrene, or a mixture of styrene and methyl methacrylate, or styrene and acrylonitrile.
[0012] Furthermore, in the above technical solution, the unsaturated carboxylic acid is selected from one or a mixture of acrylic acid, methacrylic acid, itaconic acid and fumaric acid.
[0013] Furthermore, in the above technical solution, the unsaturated amide is selected from acrylamide, methacrylamide, N,N-dimethylacrylamide, hydroxymethylacrylamide or a mixture thereof.
[0014] Furthermore, in the above technical solution, the acidified hectorite sol is composed of synthetic hectorite, a dispersant and an acidifying agent.
[0015] Furthermore, in the above technical solution, the preparation method comprises the following steps:
[0016] (1) Preparation of hectorite sol: 350 g of deionized water is added to a reactor with stirring, and when heated to 80° C., 25 g of nano hectorite and 0.5 g of dispersant are added, and the mixture is stirred and dispersed for 2 hours. Then, 2 to 4 g of citric acid or glacial acetic acid is added under stirring to adjust the pH of the solution to 3.5 to 4.0 to obtain hectorite sol;
[0017] (2) Prepolymerization: 152-365 g of the acidified hectorite sol, 10-25 g of an ethylenically unsaturated monomer, 0.04 g of a chelating agent, 0.16 g of an electrolyte, 0.5 g of a molecular weight regulator and deionized water were added to an autoclave, replaced with nitrogen and stirred at high speed, and then the temperature was raised to 80° C., and the pre-prepared initiator solution was added, and the reaction timer was started, and the reaction was allowed to proceed for 30 minutes;
[0018] (3) Continuous polymerization: After the reaction has been carried out for 30 minutes, 6-16 g of unsaturated carboxylic acid, 4-24 g of 50% aqueous solution of unsaturated amide monomer, 8-12 g of 30% aqueous solution of emulsifier, 3.5 g of molecular weight regulator, 148-208 g of C4-C5 aliphatic conjugated diene monomer and 160-232 g of a mixed solution of vinyl unsaturated monomer were added dropwise for 4 hours, and 12-26 g of 20% initiator solution were added dropwise for 5 hours. After all the additions were completed, the mixture was kept at 85° C. for 2 hours.
[0019] (4) Post-treatment stage: After slowly adding alkali to the above latex to adjust the pH to 5.0, 4-6 g of 20% tert-butyl hydroperoxide aqueous solution and 3-6 g of 20% Rongalite aqueous solution were added dropwise respectively, reacted for 4 hours, cooled and discharged, and the pH was adjusted to 6.0-7.0 to obtain the hectorite composite modified styrene-butadiene copolymer latex.
[0020] Furthermore, in the above technical solution, the dispersant is composed of modified thermoplastic polypropylene resin, acrylic resin, propylene glycol monomethyl ether acid solution, the emulsifier is sodium dodecylbenzene sulfonate, the chelating agent is sodium ethylenediaminetetraacetate (abbreviated as EDTA), the electrolyte is potassium phosphate, and the molecular weight regulator is C8-C 12 Alkyl mercaptan, the initiator is ammonium persulfate.
[0021] Furthermore, in the above technical solution, in the post-treatment stage, the tert-butyl hydroperoxide and Rongalite are redox initiators, wherein the weight ratio of tert-butyl hydroperoxide to Rongalite is 1:0.5 to 1:1.0, and the amount of tert-butyl hydroperoxide used is 50% of the total weight of the residual monomers.
[0022] Furthermore, in the above technical solution, the modified styrene-butadiene latex and the preparation method thereof are used as an adhesive in the fields of paper coating, cardboard, and non-woven fabric processing.
[0023] The invention uses laponite as one of the emulsion polymerization components and adds it into the polymerization system. The low-dimensional nanoparticle laponite with a lamellar structure is introduced into the styrene-butadiene copolymer latex through the emulsion polymerization technology. The laponite particles form a protective layer on the outer surface of the latex particles to stabilize the emulsion, thereby forming a core-shell structured water-based inorganic-styrene-butadiene copolymer paper coating material.
[0024] The modified copolymer latex of the invention has a simple preparation process, a stable reaction process, a short reaction time and a high polymerization conversion rate; the reaction process does not require a low-temperature refrigerant and a complicated monomer recovery and degassing process; the compounding of hectorite in the polymerization composition improves the physical and optical properties of the product, the latex has high nap strength, good gloss and excellent water resistance, the emulsion coating has excellent high-speed mechanical stability, chemical stability and storage stability, and no coagulant appears when stored at 10-35°C for 180 days. [Specific implementation method]
[0025] The invention discloses a modified styrene-butadiene latex, which is mainly used as an adhesive in the fields of paper coating, paperboard and non-woven fabric processing.
[0026] The weight percentage of styrene-butadiene latex composition of the present invention is:
[0027]
[0028]
[0029] The C4-C5 aliphatic conjugated diene monomer is selected from 1,3-butadiene or a mixture of 1,3-butadiene and isoprene. The vinyl unsaturated monomer is selected from styrene, or a mixture of styrene and methyl methacrylate, or styrene and acrylonitrile. The unsaturated carboxylic acid is selected from one or a mixture of acrylic acid, methacrylic acid, itaconic acid, and fumaric acid. The unsaturated amide is selected from one or a mixture of acrylamide, methacrylamide, N,N-dimethylacrylamide, and hydroxymethyl acrylamide.
[0030] The acidified hectorite sol is composed of synthetic hectorite, a dispersant and an acidifying agent. The acidified hectorite sol is prepared by dispersing, dissolving and acidifying the synthetic hectorite in two steps, the dispersant is DISPERSE-AYD W-15, and the acidifying agent is citric acid or glacial acetic acid.
[0031] In the modified styrene-butadiene latex of the invention, the copolymer latex has a solid content of 50-54%, a pH of 6.0-7.0, a viscosity of 100-300 mPa.S, a surface tension of 36-46 mN / m, a particle size of 140-166 nm, a gel content of 72-80%, and a VOC of less than 100 ppm.
[0032] The preparation method of the present invention comprises the following steps:
[0033] (1) Preparation of hectorite sol:
[0034] 350 g of deionized water is added to a reactor with stirring, and when heated to 80°C, 25 g of nano-hectorite and 0.5 g of dispersant are added, and the mixture is stirred and dispersed for 2 hours. Then, 2 to 4 g of citric acid or glacial acetic acid is added under stirring to adjust the pH of the solution to 3.5 to 4.0 to obtain hectorite sol;
[0035] (2) Prepolymerization:
[0036] 152-365 g of the acidified hectorite sol, 10-25 g of an ethylenically unsaturated monomer, 0.04 g of a chelating agent, 0.16 g of an electrolyte, 0.5 g of a molecular weight regulator and deionized water were added to a high-pressure reactor, replaced with nitrogen and stirred at high speed, and then the temperature was raised to 80° C., and the pre-configured initiator solution was added, and the reaction timer was started, and the reaction was continued for 30 minutes;
[0037] (3) Continuous polymerization:
[0038] After the reaction has been carried out for 30 minutes, 6-16 g of unsaturated carboxylic acid, 4-24 g of 50% aqueous solution of unsaturated amide monomer, 8-12 g of 30% aqueous solution of emulsifier, 3.5 g of molecular weight regulator, 148-208 g of C4-C5 aliphatic conjugated diene monomer and 160-232 g of vinyl unsaturated monomer were added dropwise for 4 hours, and 12-26 g of 20% initiator solution were added dropwise for 5 hours. After all the additions were completed, the mixture was kept at 85°C for 2 hours.
[0039] (4) Post-processing stage:
[0040] After slowly adding alkali to the above latex to adjust the pH to 5.0, 4-6 grams of 20% tert-butyl hydroperoxide aqueous solution and 3-6 grams of 20% Rongalite aqueous solution are added dropwise respectively, reacted for 4 hours, cooled and discharged, and the pH is adjusted to 6.0-7.0 to obtain the hectorite composite modified styrene-butadiene copolymer latex.
[0041] In the post-treatment stage, the tert-butyl hydroperoxide and Rongalite are redox initiators, wherein the weight ratio of tert-butyl hydroperoxide to Rongalite is 1:0.5 to 1:1.0, and the amount of tert-butyl hydroperoxide used is 50% of the total weight of the residual monomers.
[0042] In the emulsion polymerization of the present invention, in order to make the polymerization reaction proceed smoothly, the monomers can be added continuously or in batches; the unsaturated carboxylic acid can be added all at once or in batches; the emulsifier can also be added twice or semi-continuously.
[0043] In the emulsion polymerization of the present invention, various other auxiliary agents such as buffers may be added to the polymerization reaction system as required; these substances are usually used in conventional amounts.
[0044] In the present invention, the dispersant is composed of modified thermoplastic polypropylene resin, acrylic resin, and propylene glycol monomethyl ether acid solution. The emulsifier is sodium dodecylbenzene sulfonate. The chelating agent is sodium ethylenediaminetetraacetate (abbreviated as EDTA). The electrolyte is potassium phosphate. The molecular weight regulator is C8-C 12 The alkyl mercaptan is specifically tert-dodecyl mercaptan, n-dodecyl mercaptan or a mixture thereof. The initiator is ammonium persulfate.
[0045] Specifically, in the present invention, the dispersant used is Disperse-AYD W-15 dispersant, which is a Disperse-AYD series dispersant of Daniel Products Co. in the United States, and is a mixture of several surfactants, which can work synergistically to wet the pigment, resist pigment flocculation, stabilize the dispersion after coating, and have multiple functions such as the function of the dispersant. Disperse-AYD W15 is composed of modified thermoplastic polypropylene resin, acrylic resin, and propylene glycol monomethyl ether acid solution (PM Aceta), and is mainly suitable for preparing high-concentration pigment dispersions. The pigment dispersion system prepared by AYD-15 has good compatibility with various resins and can be used to prepare products with good chemical stability.
[0046] The present invention is further described below in conjunction with specific examples. The total amount of monomers added in the examples and comparative examples is measured in wt % (weight percentage).
[0047] The emulsion polymerization reaction was carried out in a stainless steel reactor which was replaced with nitrogen and equipped with a stirrer and adjustable temperature.
[0048] Example 1
[0049] 350 g of deionized water was added to a 0.5-liter reactor with stirring, and when heated to 80°C, 25 g of nano-hectorite and 0.5 g of DISPERSE-AYD W-15 dispersant were slowly added, and stirred and dispersed for 2 hours to obtain a hectorite sol after being uniformly dissolved; then, 1.05 g of citric acid was slowly added under stirring to adjust the solution pH to 3.5 to obtain an acidified hectorite sol;
[0050] 182 g of the acidified hectorite sol, 15 g of styrene, 0.04 g of EDTA chelating agent, 0.15 g of dodecyl mercaptan molecular weight regulator, and 148 g of water were added to a 1-liter autoclave, replaced with nitrogen, stirred at high speed, heated to 80°C, and then 3 g of the pre-prepared 20% ammonium persulfate initiator solution was added, the reaction timer was started, and the reaction lasted for 30 minutes.
[0051] After the reaction has been going on for 30 minutes, 14 g of acrylic acid, 18 g of 50% methacrylamide monomer aqueous solution, 11 g of 30% sodium dodecylbenzenesulfonate aqueous solution, 3.5 g of n-dodecyl mercaptan molecular weight regulator, 150 g of butadiene, 160 g of styrene and 17 g of a mixed solution of methyl styrene monomer were added dropwise for 4 hours, and 26 g of 20% ammonium persulfate solution was added dropwise for 5 hours. After all the addition was completed, the mixture was kept at 85°C for 2 hours.
[0052] After slowly adding alkali to the above latex to adjust the pH to 5.0, a redox initiation system consisting of 5 grams of a 20% aqueous solution of tert-butyl hydroperoxide and 5 grams of a 20% aqueous solution of Rongalite was added dropwise, reacted for 4 hours, cooled and discharged, and the pH was adjusted to 6.5 to obtain a core-shell structure composite modified styrene-butadiene latex.
[0053] Example 2
[0054] 350 g of deionized water was added to a 0.5-liter reactor with stirring, and when heated to 80°C, 25 g of nano-hectorite and 0.5 g of DISPERSE-AYD W-15 dispersant were slowly added, and stirred and dispersed for 2 hours to obtain a hectorite sol after being uniformly dissolved; then, 1.25 g of glacial acetic acid was slowly added under stirring to adjust the solution pH to 3.7 to obtain an acidified hectorite sol;
[0055] 330 g of the acidified hectorite sol, 25 g of styrene, 0.04 g of EDTA chelating agent, 0.15 g of dodecyl mercaptan molecular weight regulator and 65 g of deionized water were added to a 1-liter autoclave, replaced with nitrogen, stirred at high speed, heated to 80°C, and then 5 g of the pre-prepared 20% ammonium persulfate initiator solution was added, the reaction timer was started, and the reaction was continued for 30 minutes.
[0056] After the reaction has been going on for 30 minutes, 8 grams of methacrylic acid, 24 grams of 50% acrylamide monomer aqueous solution, 12 grams of 30% sodium dodecylbenzene sulfonate aqueous solution, 3.5 grams of tert-dodecyl mercaptan molecular weight regulator, 150 grams of butadiene, 40 grams of isoprene monomer and 165 grams of styrene mixed solution were added dropwise for 4 hours, and 12 grams of 20% ammonium persulfate solution were added dropwise for 5 hours. After all the addition was completed, the mixture was kept at 85°C for 2 hours.
[0057] After slowly adding alkali to the above latex to adjust the pH to 5.0, a redox initiation system consisting of 4 grams of 20% tert-butyl hydroperoxide and 5 grams of 20% Rongalite was added dropwise to react for 4 hours, the material was cooled and the pH was adjusted to 6.6 to obtain a core-shell structure composite modified styrene-butadiene latex.
[0058] Example 3
[0059] 350 g of deionized water was added to a 0.5-liter reactor with stirring. When heated to 80°C, 25 g of nano-hectorite and 0.5 g of DISPERSE-AYD W-15 dispersant were slowly added, and the mixture was stirred and dispersed for 2 hours to obtain a hectorite sol after being uniformly dissolved. Then, 0.85 g of citric acid was slowly added under stirring to adjust the pH of the solution to 4.0 to obtain an acidified hectorite sol.
[0060] 240 g of the acidified hectorite sol, 20 g of styrene, 0.04 g of EDTA chelating agent, 0.15 g of dodecyl mercaptan molecular weight regulator, and 93 g of water were added to a 1-liter autoclave, replaced with nitrogen, stirred at high speed, heated to 80°C, and then 3.5 g of the pre-prepared 20% ammonium persulfate initiator solution was added, the reaction timer was started, and the reaction was continued for 30 minutes.
[0061] After the reaction has been going on for 30 minutes, 6 g of itaconic acid was added dropwise for 4 hours, 6 g of 50% acrylamide monomer aqueous solution was added for 4 hours, 12 g of 30% sodium dodecylbenzenesulfonate aqueous solution was added for 4 hours, 3.5 g of n-dodecyl mercaptan molecular weight regulator, 160 g of butadiene, 181 g of styrene and a mixed solution of 30 g of methyl methacrylate monomer was added for 4 hours, and 26 g of 20% ammonium persulfate solution was added for 5 hours. After all the addition was completed, the mixture was kept at 85°C for 2 hours.
[0062] After slowly adding alkali to the above latex to adjust the pH to 5.0, a redox initiation system consisting of 6 grams of 20% tert-butyl hydroperoxide and 5 grams of 20% Rongalite was added dropwise to react for 4 hours, the material was cooled and the pH was adjusted to 6.3 to obtain a core-shell structure composite modified styrene-butadiene latex.
[0063] Example 4
[0064] 350 g of deionized water was added to a 0.5-liter reactor with stirring. When heated to 80°C, 25 g of nano-hectorite and 0.5 g of DISPERSE-AYD W-15 dispersant were slowly added. The mixture was stirred and dispersed for 2 hours to obtain a hectorite sol after being uniformly dissolved. Then, 1.1 g of glacial acetic acid was slowly added under stirring to adjust the pH of the solution to 4.0 to obtain an acidified hectorite sol.
[0065] 300 g of the above-mentioned acidified hectorite sol, 20 g of styrene, 0.04 g of EDTA chelating agent, 0.15 g of dodecyl mercaptan molecular weight regulator and 74 g of deionized water were added to a 1-liter autoclave, replaced with nitrogen, stirred at high speed, heated to 80°C, then 4.5 g of the pre-configured 20% ammonium persulfate initiator solution was added, the reaction timer was started, and the reaction was completed after 30 minutes.
[0066] After the reaction has been going on for 30 minutes, 14 g of acrylic acid, 4 g of 50% aqueous solution of hydroxymethyl acrylamide monomer were added dropwise for 4 hours, 8 g of 30% aqueous solution of sodium dodecylbenzene sulfonate emulsifier were added dropwise for 3 hours, 3.5 g of a mixed solution of tert-dodecyl mercaptan molecular weight regulator, 172 g of butadiene monomer and 192 g of styrene monomer were added dropwise for 4 hours, and 140 g of a 20% ammonium persulfate solution was added dropwise for 5 hours. After all the additions were completed, the mixture was kept warm at 85°C for 2 hours.
[0067] After slowly adding alkali to the latex to adjust the pH to 5.0, a redox initiation system consisting of 4.0 g of 20% tert-butyl hydroperoxide and 3.5 g of 20% Rongalite was added dropwise to react for 4 hours, the material was cooled and the pH was adjusted to 6.5 to obtain a core-shell structure composite modified styrene-butadiene latex.
[0068] Example 5
[0069] 350 g of deionized water was added to a 0.5-liter reactor with stirring. When heated to 80°C, 25 g of nano-hectorite and 0.5 g of DISPERSE-AYD W-15 dispersant were slowly added, and the mixture was stirred and dispersed for 2 hours to obtain a hectorite sol after being uniformly dissolved. Then, 1.2 g of citric acid was slowly added under stirring to adjust the solution pH to 3.8 to obtain an acidified hectorite sol.
[0070] 325 g of the above-mentioned acidified hectorite sol, 23 g of styrene, 0.04 g of EDTA chelating agent, 0.15 g of dodecyl mercaptan molecular weight regulator, and 24 g of water were added to a 1-liter autoclave, replaced with nitrogen, stirred at high speed, heated to 80°C, and then 4.5 g of the pre-configured 20% ammonium persulfate initiator solution was added, the reaction timer was started, and the reaction was completed after 30 minutes.
[0071] After the reaction has been going on for 30 minutes, 8 g of fumaric acid, 20 g of 50% aqueous solution of hydroxymethyl acrylamide monomer were added dropwise for 4 hours, 10 g of 30% aqueous solution of dodecyl diphenyl oxide disulfonate emulsifier were added dropwise for 3 hours, 3.5 g of tert-dodecyl mercaptan molecular weight regulator, 163 g of butadiene monomer, 190 g of styrene monomer and 6 g of acrylonitrile were added dropwise for 4 hours, and 16 g of 20% ammonium persulfate solution were added dropwise for 5 hours. After all the additions were completed, the mixture was kept at 85°C for 2 hours.
[0072] After slowly adding alkali to the above latex to adjust the pH to 5.0, a redox initiation system consisting of 4 grams of a 20% aqueous solution of tert-butyl hydroperoxide and 3.5 grams of a 20% aqueous solution of Rongalite was added dropwise, reacted for 4 hours, cooled and discharged, and the pH was adjusted to 6.3 to obtain a core-shell structured composite modified styrene-butadiene latex.
[0073] Example 6
[0074] 350 g of deionized water was added to a 0.5-liter reactor with stirring, and when heated to 80°C, 25 g of nano-hectorite and 0.5 g of DISPERSE-AYD W-15 dispersant were slowly added, and stirred and dispersed for 2 hours to obtain a hectorite sol after being uniformly dissolved; then, 1.05 g of glacial acetic acid was slowly added under stirring to adjust the solution pH to 3.6 to obtain an acidified hectorite sol;
[0075] 305 g of the acidified hectorite sol, 25 g of styrene, 0.04 g of EDTA chelating agent, 0.15 g of dodecyl mercaptan molecular weight regulator, and 25 g of water were added to a 1-liter autoclave, replaced with nitrogen, stirred at high speed, heated to 80°C, and then 6 g of the pre-prepared 20% ammonium persulfate initiator solution was added, the reaction timer was started, and the reaction was continued for 30 minutes.
[0076] After the reaction has been going on for 30 minutes, 16 g of acrylic acid, 6 g of 50% N,N-dimethylacrylamide aqueous solution, 8 g of 30% dodecyl diphenyl ether disulfonate aqueous solution, 3.5 g of tert-dodecyl mercaptan molecular weight regulator, 178 g of butadiene, 6 g of acrylonitrile monomer and 172 g of styrene mixed solution were added dropwise for 4 hours, and 26 g of 20% ammonium persulfate solution was added dropwise for 5 hours. After all the addition was completed, the mixture was kept at 85°C for 2 hours.
[0077] After slowly adding alkali to the latex to adjust the pH to 5.0, a redox initiation system consisting of 5 g of 20% tert-butyl hydroperoxide and 5 g of 20% Rongalite was added dropwise to react for 4 hours, the material was cooled and the pH was adjusted to 6.5 to obtain a core-shell structured composite modified styrene-butadiene latex.
[0078] Comparative Example 1
[0079] Except that the dispersant DISPERSE-AYD W-15 is not used in the preparation of the acidified hectorite sol, the rest is the same as in Example 1. Comparative Example 2
[0080] The same procedures as in Example 1 were followed except that citric acid was not used in the preparation of the acidified hectorite sol.
[0081] Comparative Example 3
[0082] Except that the laponite sol is not acidified in the prepolymerization, the rest is the same as in Example 1.
[0083] The physical properties of the styrene-butadiene latex obtained in Examples 1 to 6 and Comparative Examples 1 to 3 and the properties of the paper coatings prepared therefrom for use in lightweight paper coatings are shown in Table 1.
[0084] Table 1
[0085]
[0086] From the mechanical stability, chemical stability and storage stability, it can be seen that compared with Comparative Examples 1 to 3, Examples 1 to 6 have better stability performance (the lower the value, the better the stability; mechanical stability ≤0.03% is qualified, chemical stability ≤0.03% is qualified, and storage stability ≤0.02% is qualified); compared with Comparative Examples 1 to 3, the roughening strength and low gloss performance of the coated paper of Examples 1 to 6 are excellent, and the roughening strength or gloss of Comparative Examples 1 to 3 is relatively low.
[0087] The above is a better technical solution for the embodiment of the present invention. The above embodiment is only used to illustrate the technical solution of the embodiment of the present invention, and does not limit it. It is understood by ordinary technicians in this field that the technical solution of the embodiment of the present invention can still be modified or replaced by equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the scope of the technical plan of the embodiment of the present invention.
Claims
1. A modified styrene-butadiene latex, characterized in that: The weight percentage of this styrene-butadiene latex composition is: 37-52% of C4-C5 aliphatic conjugated diene monomers; Ethylene unsaturated monomer 40-58%; Acidified hectorite sol 2.5-6.0%; Unsaturated carboxylic acid monomer 1.5-4.0%; Unsaturated amide monomer 0.5-3.0%; The acidified hectorite sol is composed of synthetic hectorite, a dispersant and an acidifying agent. The acidified hectorite sol is prepared by dispersing, dissolving and acidifying the synthetic hectorite in two steps. The dispersant is DISPERSE-AYD W-15, and the acidifying agent is citric acid or glacial acetic acid.
2. A modified styrene-butadiene latex according to claim 1, characterized in that: The C4-C5 aliphatic conjugated diene monomer is selected from 1,3-butadiene or a mixture of 1,3-butadiene and isoprene.
3. A modified styrene-butadiene latex according to claim 1, characterized in that: The vinyl unsaturated monomer is selected from styrene, or a mixture of styrene and methyl methacrylate, or styrene and acrylonitrile.
4. The modified styrene-butadiene latex according to claim 1, characterized in that: The unsaturated carboxylic acid is selected from one or a mixture of acrylic acid, methacrylic acid, itaconic acid and fumaric acid.
5. The modified styrene-butadiene latex according to claim 1, characterized in that: The unsaturated amide is selected from acrylamide, methacrylamide, N,N-dimethylacrylamide, hydroxymethylacrylamide or a mixture thereof.
6. A modified styrene-butadiene latex according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) Preparation of acidified lithium soapstone sol: 350 g of deionized water is added to a reactor with stirring, and when heated to 80°C, 25 g of nano-hectorite and 0.5 g of dispersant are added, and the mixture is stirred and dispersed for 2 hours. Then, 2 to 4 g of citric acid or glacial acetic acid is added under stirring to adjust the pH of the solution to 3.5 to 4.0 to obtain an acidified hectorite sol; (2) Prepolymerization: 152-365 g of the acidified hectorite sol, 10-25 g of an ethylenically unsaturated monomer, 0.04 g of a chelating agent, 0.16 g of an electrolyte, 0.5 g of a molecular weight regulator and deionized water were added to a high-pressure reactor, replaced with nitrogen and stirred at high speed, and then the temperature was raised to 80° C., and the pre-configured initiator solution was added, and the reaction timer was started, and the reaction was continued for 30 minutes; (3) Continuous polymerization: After the reaction has been carried out for 30 minutes, 6 to 16 grams of unsaturated carboxylic acid are added dropwise for 4 hours, 4 to 24 grams of 50% aqueous solution of unsaturated amide monomer is added dropwise for 4 hours, 8 to 12 grams of 30% aqueous solution of emulsifier is added dropwise for 4 hours, 3.5 grams of molecular weight regulator, 148 to 208 grams of C4 to C5 aliphatic conjugated diene monomer and 160 to 232 grams of a mixed solution of vinyl unsaturated monomer are added dropwise for 4 hours, and 12 to 26 grams of 20% initiator solution are added dropwise for 5 hours. After all the additions are completed, the mixture is kept at 85° C. for 2 hours. (4) Post-processing stage: After slowly adding alkali to the latex to adjust the pH to 5.0, 4-6 g of 20% tert-butyl hydroperoxide aqueous solution and 3-6 g of 20% Rongalite aqueous solution were added dropwise respectively, reacted for 4 hours, cooled and discharged, and the pH was adjusted to 6.0-7.0 to obtain a hectorite composite modified styrene-butadiene copolymer latex; The above percentages are percentages by weight.
7. The modified styrene-butadiene latex according to claim 6, characterized in that: The dispersant is composed of modified thermoplastic polypropylene resin, acrylic resin, propylene glycol monomethyl ether acid solution, the emulsifier is sodium dodecylbenzene sulfonate, the chelating agent is sodium ethylenediaminetetraacetate, the electrolyte is potassium phosphate, and the molecular weight regulator is C8-C 12 Alkyl mercaptan, the initiator is ammonium persulfate.
8. The modified styrene-butadiene latex according to claim 6, characterized in that: In the post-treatment stage, the tert-butyl hydroperoxide and Rongalite are redox initiators, wherein the weight ratio of tert-butyl hydroperoxide to Rongalite is 1:0.5 to 1:1.0, and the amount of tert-butyl hydroperoxide used is 50% of the total weight of the residual monomers.
9. The modified styrene-butadiene latex according to claim 6, characterized in that: The modified styrene-butadiene latex is used as an adhesive in the fields of paper coating, cardboard and non-woven fabric processing.
Citation Information
Patent Citations
Styrene-butadiene emulsion modified by sodium-base bentonite, and preparation method and application thereof
CN101381486B
Novel waterborne acrylic acid resin / Li-based bentonite composite leather finishing agent prepared through Pickering emulsion polymerization technology
CN107880207A
Multiphase structure styrene-butadiene latex for paper coating and preparation method and application thereof
CN110483673A
Butadiene-styrene copolymer latex for paper coating as well as preparation method and application thereof
CN110483674A
A butadiene-styrene copolymer latex, its preparation method and application
CN110483675B